Guillain-Barre syndrome in an adult patient with Henoch-Schonlein purpura. (3rd April 2013) - Aggarwal, Puneet; Sahoo, Ratnakar; Gadpayle, A K; Kumar, Gunjan
Abstract : A 42-year-old man presented with pain in the abdomen, massive haematemesis and rashes over the body and development of bilateral lower limb weakness the next day. The patient was later diagnosed with Guillain-Barre syndrome with Henoch-Schonlein purpura. He was treated with intravenous immunoglobulins. At 3 months of follow-up and rehabilitation, patient showed complete recovery from weakness.